Modelling the development of capillary pressure in freshly 3D-printed concrete elements. (July 2021) - Ghourchian, Sadegh; Butler, Marko; Krüger, Markus; Mechtcherine, Viktor
Abstract: 3D concrete printing is a promising technology recently developed to automate construction. Since no formwork is used in this technology to support and protect fresh concrete, there are two aspects which considerably accelerate the development of capillary pressure in 3D-printed concrete in comparison to conventionally placed concrete: i) high stiffness of 3D-printed needed to provide sufficient buildability, and ii) very early and fast evaporation of pore water. Accelerated development of capillary pressure may lead to severe plastic shrinkage cracking in 3D-printed elements and, hence, need to be mitigated. This investigation aims at providing a poromechanical model for capillary pressure development in 3D-printed elements. To simulate the development of capillary pressure and plastic shrinkage, environmental factors, material properties, and element geometry need to be considered as a whole. The model inputs – coefficient of permeability, static bulk modulus, air entry pressure and chemical shrinkage rate – were determined experimentally. The model was validated for two fine-grained concretes. Both 3D-printed materials yielded faster capillary pressure increase in comparison to cast concrete, while partial substitution of cement with silica fume further accelerated the capillary pressure development. Furthermore, due to the lower permeability of the mixture containing silica fume, the gradient of capillary pressure between 3D-printed layers increased, as did the gradient of plastic shrinkage.